Aspek Hukum Perlindungan Bagi Nasabah dalam Menghadapi Ancaman Cybercrime Penggunaan Internet Banking - Alda Alda; Winda Sari (Universitas Katolik Widya Karya Malang, 2023)
There are still many legal violations regarding personal data via the internet and also regarding the financial risks suffered by bank customers. There are regulations that protect bank customers who use internet banking from the threat of cyber crime and what legal measures can be taken by bank customers who use internet banking if the customer's personal data is not protected or their personal data is leaked. The research design or structure used by the author in this research is Library Research. There are several laws and regulations that regulate the personal data of customers and also banks and bank customers who feel disadvantaged due to the dissemination of customer personal information. That legal protection efforts have been made but have not reflected the principle of balance that is needed. Bank customers who feel disadvantaged due to the distribution of customer personal information used by third parties. The need for better legal protection for customers.